Implementation of Drill and Jigsaw Methods in Improving Learning Outcomes of Fiqh of Worship Material at Madrasah Aliyah Raudhatut Thullab Siak Kecil - Wiwie; Gusriani, Wira; Sugiarti, Wiwi; Winda; Winarti (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to examine the effectiveness of the implementation of the Drill and Jigsaw method in improving student learning outcomes in the Fiqh Ibadah subject in grade 10 of Madrasah Aliyah Raudhatut Thullab, Siak Kecil, Bengkalis. The Drill method focuses on repetitive exercises to strengthen understanding of concepts and skills, while the Jigsaw method encourages collaborative learning by dividing materials into small groups that share information. This study uses a quantitative approach with an experimental design, where the class is divided into an experimental group using the Drill and Jigsaw method and a control group using the conventional method. Data collection was carried out through learning outcome tests, observations, and interviews. The results showed that students who studied with a combination of the Drill and Jigsaw method experienced better improvements in understanding and skills than students who used the conventional method. In addition, this method also increases students' active participation in the learning process, as well as encouraging cooperation and communication skills. These findings indicate that the integration of the Drill and Jigsaw method can be an effective learning strategy in improving Fiqh Ibadah learning outcomes at the Madrasah Aliyah level.